Flow-activated proximal tubule function underlies glomerulotubular balance - Du, Zhaopeng (Kitasato Med J, 2016)
Flow-modulated salt and water transport in proximal tubules has been recognized for more than four decades. Recent work has made major progress in defining the underlying cellular mechanisms. First, we demonstrated that perfusion-absorption balance is present in the isolated perfused proximal tubule of the mouse kidney, and thus is independent of neuronal control and systemic hormonal regulation. In proximal tubule, higher axial flow rates stimulate sodium and bicarbonate absorption by increased apical membrane Na(+)/H(+)-transporter and H-ATPase activity. It is also evident that fluid shear stress stimulates Na(+)/H(+) exchanger isoform 3 (NHE3) exocytosis and trafficking to the apical membrane of the proximal tubule cells. Second, experimental data and modeling calculations provide strong evidence that brush border microvilli function as flow sensors in the proximal tubule. Flow-induced changes of proximal tubule absorption depend on the changes of torque (bending moment) on the microvilli, and that an intact actin cytoskeleton is required to transduce signals from the brush border to cell and alter transport activity, NHE3 expression and trafficking. Third, the increased NHE3 exocytosis by dopamine blockers enhanced tubule sensitivity to torque, and the IP(3) receptor-mediated intracellular Ca(2+) signaling is a critical step in transduction of fluid drag on microvillus drag tips in modulating Na(+) and HCO(3)(−) transport. Finally, in all of our experimental studies, flow-dependent transport in mouse tubules was achieved with virtually no change in tubule cell volume. Our model calculations suggest that this observation is strong evidence for proportional luminal and peritubular effects of flow on transporter density.